Penerapan Model PBL pada Materi Relasi dan Fungsi untuk Melihat Nilai Kreatif Siswa Kelas VIII - Wardhani, Novia Kusuma; Aisyah, Nyimas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
Students' creative value is still relatively low because teaching and learning activities in schools are still conventional, monotonous or teacher-centered so that students' creative value is not optimal. One of the right ways to optimize students' creative values ​​is to choose the right learning model to integrate creative values, such as the PBL model. This research aims to describe the creative value of junior high school students in the PBL learning model on relationship and function material. Researchers used qualitative descriptive methods. The main focus of creative values ​​in this research is the creative values ​​of originality and creative flexibility. The subjects of this research were class VIII students at SMP Negeri 45 Palembang using written test instruments. Data was collected through tests which were then analyzed descriptively qualitatively. Researchers obtained research results that the creative value that most often appears in the learning of relationship and function material is creative originality, while the creative value that rarely appears is the creative value of flexibility.